Intangibles in light of industry-level CompNet dataset - Pikka Aleksi (The Research Institute of the Finnish Economy (ETLA), 2024)
This paper studies the productivity effects of intangible assets using 9th vintage of the CompNet dataset. Descriptive work shows that there is dispersion in usage of intangibles; some firms invest heavily into intangible assets and many firms do not invest at all. In addition, preliminary evidence, using the joint distributions provided by CompNet, implies that intangible assets increase the productivity of the firms that already belong to the 90th productivity percentile. Furthermore, I estimate the output elasticity of intangible assets by a Cobb Douglas production function using data at the 2-digit industry (NACE rev 2) level of aggregation and find output elasticity of intangibles to be approximately between 0.08-0.10. A special emphasis is placed on development of intangibles in Finland. I find that concentration in intangibles, measured by the Herfindahl-Hirschman index, has increased in the past few years and that intangible assets are concentrated in ICT and manufacturing macro-sectors. In addition, I estimate a Cobb Douglas production function using only data from Finland and find that while output elasticity on intangible assets is approximately 0.05, the coefficient is not statistically significant, and hence, the evidence is inconclusive.
Keywords: E22; J24; O52; 330; Intangible capital; Productivity